The Analysis Study of Effectiveness and Safety of Topical Treatment for Vernal Keratoconjunctivitis: A Comprehensive Systematic Review - Fazri, Karin Ananditya; Ramadhani, Fikar (The International Journal of Medical Science and Health Research, 2024)
Background: This systematic review aims to evaluate and synthesize evidence on the efficacy and safety of topical treatments for VKC, focusing on the effectiveness of treatments like cyclosporine A, tacrolimus, and other topical therapies in alleviating symptoms and improving clinical outcomes. Methods: The review followed PRISMA 2020 guidelines, including studies published in English from 2014 to 2024. Results: Eight studies met the inclusion criteria. The review found that both cyclosporine A and tacrolimus significantly reduced symptom and sign scores in VKC patients. Rebamipide was comparable in efficacy to cyclosporine and tacrolimus. Tacrolimus showed efficacy in corticosteroid-refractory cases, while cyclosporine A reduced steroid dependency and related side effects. Conclusion: Topical cyclosporine A and tacrolimus are effective in managing VKC, with improvements in symptoms and clinical signs observed across studies. Cyclosporine A is particularly effective in reducing reliance on corticosteroids, while tacrolimus is beneficial for corticosteroid-refractory VKC. Personalized treatment strategies should be considered based on individual patient responses and tolerability.